Factors that influence dividend payment: profitibility & liquidity / Ahmad Farouk Zulkifli - Zulkifli, Ahmad Farouk (Faculty of Business Management, 2017)
This study is carried out to study the relationship of profitability and liquidity toward dividend payment of public listed companies in Malaysia. The study is carried out by analyzing the relationship between earning per share, return on equity and cash flow per share toward dividend per share. Data for this study were obtained from relevant databases and annual reports of the sampled companies. The study determines 20 dividend paying companies listed in Bursa Malaysia for the year 2006 to 2015. Starting the year 2006, the Federal Government of Malaysia announced a series of five economic corridors in an attempt to stimulate global and domestic investment in traditionally rural areas to create balanced development throughout the country. The data of this research starting from 2006 to 2015 is being observed in order to foresee the impact of the economy corridors parallel with the factors that influence dividend payment of dividend paying companies. The results proved that the three factors which are return on equity, earning per share, and cash flow per share have a relationship with dividend payment, with return on equity, earning per share and cash flow per share revealed to have a significant relationship. The findings from this research are useful to the board of directors and management team of companies in deciding an appropriate dividend payment for the company. The results will also benefits shareholders in making investment decisions. The study adds factual evidence on factors of dividend payment which are currently reported to be inconclusive. Moreover, the study improvise the existing literature by focusing on the issue of factors of dividend payment in the context of Malaysia.